2008
DOI: 10.1016/j.mod.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the endoplasmic reticulum calcium pump during zebrafish gastrulation affects left–right asymmetry of the heart and brain

Abstract: Vertebrate embryos generate striking Ca(2+) patterns, which are unique regulators of dynamic developmental events. In the present study, we used zebrafish embryos as a model system to examine the developmental roles of Ca(2+) during gastrulation. We found that gastrula stage embryos maintain a distinct pattern of cytosolic Ca(2+) along the dorsal-ventral axis, with higher Ca(2+) concentrations in the ventral margin and lower Ca(2+) concentrations in the dorsal margin and dorsal forerunner cells. Suppression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…In zebrafish, motile cilia in Kupffer's vesicle (KV) appear to be crucial for left-right asymmetry, analogous to their counterparts in the node in amniotes (Amack et al, 2007;Amack and Yost, 2004). Evidence gathered from both zebrafish and mouse embryos suggests a strong connection between node/vesicle structures and proper left-right patterning, especially with regard to the flow-generating function of primary cilia (Amack et al, 2007;Amack and Yost, 2004;Kreiling et al, 2008;Marszalek et al, 1999;Murcia et al, 2000;Nonaka et al, 1998;Okada et al, 1999;Schneider et al, 2008;Supp et al, 1999;Takeda et al, 1999). We therefore tested for KV defects in the miR-92 morphants.…”
Section: Depletion Of Mir-92 Results In Aberrant Left-right Patterninmentioning
confidence: 99%
“…In zebrafish, motile cilia in Kupffer's vesicle (KV) appear to be crucial for left-right asymmetry, analogous to their counterparts in the node in amniotes (Amack et al, 2007;Amack and Yost, 2004). Evidence gathered from both zebrafish and mouse embryos suggests a strong connection between node/vesicle structures and proper left-right patterning, especially with regard to the flow-generating function of primary cilia (Amack et al, 2007;Amack and Yost, 2004;Kreiling et al, 2008;Marszalek et al, 1999;Murcia et al, 2000;Nonaka et al, 1998;Okada et al, 1999;Schneider et al, 2008;Supp et al, 1999;Takeda et al, 1999). We therefore tested for KV defects in the miR-92 morphants.…”
Section: Depletion Of Mir-92 Results In Aberrant Left-right Patterninmentioning
confidence: 99%
“…Early zebrafish development has not yet been sufficiently probed, despite the recent discovery of interesting ''orphan'' pathway members such as endoplasmic reticulum ion transporters (Kreiling et al, 2008) and evidence indicating the dorsalventral axis is established at the second cleavage (Gore et al, 2005). Moving forward will require increased collaboration among labs with expertise in specific pathways and model systems to cross-check their pathways in a wider variety of taxa, and remaining open to the idea that the origin problem is not yet solved.…”
Section: Major Open Issuesmentioning
confidence: 99%
“…Calcium ions have been involved in left-right patterning of embryos in zebrafish, Xenopus laevis and mouse (McGrath et al, 2003;Kreiling et al, 2008;Lewis et al, 2009), in left-right determination by means of Notch signaling in chick embryos (Raya et al, 2004), and in the mediation of morphogenetic movements during neural tube formation in axolotl (Moran, 1990). Although no exact data exist on whether Ca 2þ ion kinetics have a specific function in tissue regeneration in vivo, various in vitro studies have suggested that Ca 2þ ions/channels are necessary for this process (Unlu et al, 2002;Nicou et al, 2007).…”
Section: Calciummentioning
confidence: 99%